Organizational implications for mainstreaming participatory research and gender analysis - Gurung, Barun (International Development Research Centre, 2005)
T he effectiveness of Participatory Research and Gender Analysis (PR&GA) approaches is critically constrained by an organizational structure based on a supply-driven system of innovation. Results of several studies conducted by the Program with the Consultative Group on International Agricultural Research (CGIAR) centers demonstrates three separate but inter-related constraints: 1) Fragmented investment in and application of PR&GA approaches across the CGIAR system leads to repeated testing of proven approaches and as a result of which international agricultural research centers (IARCs) do not evolve beyond a researcher-led type of participation. 2) In a researcher-driven participatory research process, the likelihood of technologies matching farmers’ priorities is small because end-users, such as women, tend to be brought into the participatory research process at a relatively late stage, to evaluate technologies that have already been developed and are ready for dissemination. 3) Even in those cases where innovations have resulted from farmers’ feedback, it is unlikely that such learning and change can be sustained beyond the life of the project. One major reason for this is that PR&GA approaches largely remain isolated from, and often contradict the dominant paradigm of innovation practiced within organizations.